(untitled) (Al-Qamar, 2020)
The Muhaddithin collected the hadiths of the Prophet and also made rules for examining the authenticity and weakness of these hadiths. The hadith scholars compiled various books of hadiths and also mentioned the narrators of each hadith in them. The scholars of Asma-ul-Rijal examined these narrators on the principles of Jarh wa Tadeel. But the authenticity of the hadiths of Sira has not been examined as a hadith. That is why now a large part of the narrations of Sirah are deprived of this research and many Ahaith of sīrah are found to be weak and unreliable matter. These hadiths were also written in the Urdu books of Sira. Are and they are unreliable. This article will review some unreliable hadith incidents in Urdu books of Sira.